P3_4 Keeping your head in the clouds - Perry, Michael; Clarke, Iain; Bettles, John; Pilkington, Nathan (Physics Special Topics, 2011)
Â An investigation into whether the ship "Cloudbase" from the Captain Scarlet TV series could actually maintain stationary altitude. The weight of the Cloudbase structure was calculated to be 3.22x1010N assuming it is mostly comprised of carbon fibre, it would need a power of 1.61x1013W to run the engines alone equivalent to roughly 644 thousand nuclear power plants. This idea was determined infeasible.